Alaska's Changing Boreal Forest: Bonanza Creek, Alaska - DeFrantz, Thomas F; Oswood, Mark W; Cleve, Keith van; Viereck, Leslie A; Verbyla, David L (Oxford University Press, Incorporated, 2006)
PART I: Alaska's Past and Present Environment1. The Conceptual Basis of LTER Studies in the Alaskan Boreal Forest2. Regional Overview of Interior Alaska3. State Factor Control of Soil Formation in Interior Alaska4. Climate and Permafrost Dynamics of the Alaskan Boreal Forest5. Holocene Development of the Alaskan Boreal ForestPART II: Forest Dynamics6. Floristic Diversity and Distribution in the Alaskan Boreal Forest7. Successional Processes in the Alaskan Boreal Forest8. Mammalian Herbivore Population Dynamics in the Alaskan Boreal Forest9. Dynamics of Phytophagous Insects and Their Pathogens in Alaskan Boreal Forests10. Running Waters of the Alaskan Boreal ForestPART III: Ecosystem Dynamics11. Controls over Forest Production in Interior Alaska12. The Role of Fine Roots in the Functioning of Alaskan Boreal Forests13. Mammalian Herbivory, Ecosystem Engineering and Ecological Cascades in Alaskan Boreal Forests14. Microbial Processes in the Alaskan Boreal Forest15. Patterns of Biogeochemistry in Alaskan Boreal ForestsPART IV: Changing Regional Processes16. Watershed Hydrology and Chemistry in the Alaskan Boreal Forest: The Central Role of Permafrost17. Fire Trends in the Alaskan Boreal Forest18. Timber Harvest in Interior Alaska19. Climate Feedbacks in the Alaskan Boreal Forest20. Communication of Alaskan Boreal Science with Broader Communities21. Summary and Synthesis: Past and Future Changes in the Alaskan Boreal Forest.